1991
DOI: 10.1073/pnas.88.9.3574
|View full text |Cite
|
Sign up to set email alerts
|

The CDC7 protein of Saccharomyces cerevisiae is a phosphoprotein that contains protein kinase activity.

Abstract: The CDC7 protein of Saccharomyces cerevisiae may be involved in the G1/S-phase transition and/or in the initiation of mitotic DNA synthesis. The CDC7 gene has two in-frame AUG codons as possible translation start sites, which would produce 58-and 56-kDa proteins, respectively. Both p58 and p56 derived from recombinant plasmids complement the temperature-sensitive growth defect of the cdc7-1 allele. To determine the biochemical function of the CDC7 protein, the CDC7 gene was cloned and polyclonal antibodies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 25 publications
2
43
0
Order By: Relevance
“…Cdc7-related proteins are known to localize to the nucleus (34,59,72). Likewise, Spo4 was detected in nuclei of meiotic cells, relatively abundantly in mono-and binucleate cells and less so in tetranucleate cells.…”
Section: Discussionmentioning
confidence: 90%
“…Cdc7-related proteins are known to localize to the nucleus (34,59,72). Likewise, Spo4 was detected in nuclei of meiotic cells, relatively abundantly in mono-and binucleate cells and less so in tetranucleate cells.…”
Section: Discussionmentioning
confidence: 90%
“…After 2 and 4 h, pol2 mutant F cells were fixed in ethanol (for nuclear morphology) or formaldehyde (for tubulin morphology). The nucleoid was observed using 4Ј,6-diamino-2-phenylindole (DAPI), and spindle morphology was determined using anti-␣-tubulin antibody (9,42,43). studies have recently dissected the damage response into two different branches and revealed that the Pol2 pathway responds to damage only during S phase, whereas Rad9 responds to damage in other phases of the cell cycle (10).)…”
Section: Mutations In Zf1 and Between Zf1 And Zf2 Show Reduced Inducimentioning
confidence: 99%
“…It is not known if Cdc7 and Cdk2-Cyclin E function in a parallel pathway or in the same pathway for S phase initiation. Results in budding yeast have suggested that Cdc7 may be regulated by phosphorylation of the conserved threonine present near the APE motif (Thr-281), although the kinase responsible for this phosphorylation has not been known (18,19,41).…”
mentioning
confidence: 99%